The effect of nitric oxide on MCF-7 breast cancer cells / Nur Atika Abdul Manap - Abdul Manap, Nur Atika (2014)
SNP is widely used as an emergency anti-hypertensive. It is a short-acting NO. donor. NO. has a single unpaired electron and is therefore called as a free radical. It has a half-life of only 5-6 seconds. NO. activates guanylate cyclase in vascular smooth muscle and causes an increase in production of cGMP. This eventually leads to vasodilation. Recently, tamoxifen is used as a treatment for ER+ by blocking the ER. Here we studied the used of SNP as an alternative way to treat ER+ BC. In MCF-7 cells, NO. release by SNP was targeted to interact directly with IRP and caused a conformational change of the protein, which mimicked the effect of Fe starvation. At high concentration of NO. release by this SNP, it was expected to cause an accumulation of p53 and eventually lead to a programmed cell death. We hypothesised that NO. can cause cytotoxicity to MCF-7 at micromolar concentration. Two different assays were carried out in order to prove this hypothesis. Griess assay was performed to indirectly measure the concentration of NO. release by SNP while MTT assay was performed to measure the percentage of cell viability. We concluded that NO. did not cause cytotoxicity to MCF- 7 as there was no significant difference in the percentage of cell viability as the cells were treated with SNP.